Immune responses in beta-thalassaemia: heme oxygenase 1 reduces cytokine production and bactericidal activity of human leucocytes - Nithichanon, Arnone (Sci Rep, 2020)
Patients with beta-thalassaemia increase the risk of bacterial infections, particularly Burkholderia pseudomallei (Bp), the causative agent of melioidosis in Thailand. Impaired immune cell functions may be the cause of this susceptibility, but detailed mechanisms have not been defined. In this study, we observed impaired production of IFN-gamma and IL-10 by whole blood from beta-thalassaemia patients upon stimulation with a range of bacteria-derived stimuli. In contrast, IFN-gamma response via TCR and plasma IgG specific for Bp were still intact. Importantly, mRNA expression of heme oxygenase 1 (HO-1), a potential modulator of immune function, was increased in whole blood from beta-thalassaemia patients, either with or without stimulation with Bp in vitro. Induction of HO-1 by hemin or CoPP in vitro reduced production of IFN-gamma and IL-10 from healthy human PBMCs and decreased bacterial clearance activity of whole blood from healthy controls and beta-thalassaemia, while inhibition of HO-1 by SnPP enhanced both functions in healthy controls. These results were confirmed to some extent in purified human monocytes of healthy controls. Our results suggest a mechanism that excess hemin of beta-thalassaemia patients is a significant cause of immune suppression via HO-1 induction and may underlie the susceptibility of these individuals to severe bacterial infection.